Association of Educational, Occupational and Socioeconomic Status with Cardiovascular Risk Factors in Asian Indians: A Cross-Sectional Study - Gupta, Rajeev; Deedwania, Prakash C.; Sharma, Krishnakumar; Gupta, Arvind; Guptha, Soneil; Achari, Vijay; Asirvatham, Arthur J.; Bhansali, Anil; Gupta, Balkishan; Gupta, Sunil; Jali, Mallikarjuna V.; Mahanta, Tulika G.; et al. (PloS one, 2012)
To determine correlation of multiple parameters of socioeconomic status with cardiovascular risk factors in India. The study was performed at eleven cities using cluster sampling. Subjects (n = 6198, men 3426, women 2772) were evaluated for socioeconomic, demographic, biophysical and biochemical factors. They were classified into low, medium and high socioeconomic groups based on educational level (<10, 10-15 and >15 yr formal education), occupational class and socioeconomic scale. Risk factor differences were evaluated using multivariate logistic regression. Age-adjusted prevalence (%) of risk factors in men and women was overweight or obesity in 41.1 and 45.2, obesity 8.3 and 15.8, high waist circumference 35.7 and 57.5, high waist-hip ratio 69.0 and 83.8, hypertension 32.5 and 30.4, hypercholesterolemia 24.8 and 25.3, low HDL cholesterol 34.1 and 35.1, high triglycerides 41.2 and 31.5, diabetes 16.7 and 14.4 and metabolic syndrome in 32.2 and 40.4 percent. Lifestyle factors were smoking 12.0 and 0.5, other tobacco use 12.7 and 6.3, high fat intake 51.2 and 48.2, low fruits/vegetables intake 25.3 and 28.9, and physical inactivity in 38.8 and 46.1%. Prevalence of > = 3 risk factors was significantly greater in low (28.0%) vs. middle (23.9%) or high (22.1%) educational groups (p<0.01). In low vs. high educational groups there was greater prevalence of high waist-hip ratio (odds ratio 2.18, confidence interval 1.65-2.71), low HDL cholesterol (1.51, 1.27-1.80), hypertriglyceridemia (1.16, 0.99-1.37), smoking/tobacco use (3.27, 2.66-4.01), and low physical activity (1.15, 0.97-1.37); and lower prevalence of high fat diet (0.47, 0.38-0.57),overweight/obesity (0.68, 0.58-0.80) and hypercholesterolemia (0.79, 0.66-0.94). Similar associations were observed with occupational and socioeconomic status. Low educational, occupational and socioeconomic status Asian Indians have greater prevalence of truncal obesity, low HDL cholesterol, hypertriglyceridemia, smoking or tobacco use and low physical activity and clustering of > = 3 major cardiovascular risk factors.